Physicochemical investigation of N-ethyl-2-pyrrolidone with ethanolamine and diethanolamine systems at different temperatures - Anjali Awasthi (Chemical Thermodynamics and Thermal Analysis)
The physicochemical properties such as intermolecular free length (Lf), Debye temperature (θD), pseudo-Gruneisen parameter (Γ), isobaric thermal expansivity (α) and internal pressure (Pin) were estimated for binary mixtures of N-ethyl-2-pyrrolidone with ethanolamine and diethanolamine, over the entire composition range and at temperatures 293.15, 303.15, 313.15 and 323.15 K. The deviation in ultrasonic speed (Δu), excess intermolecular free length (LfE), excess acoustic impedance (ZE), excess Debye temperature (θDE), excess pseudo-Gruneisen parameter (ΓE) and excess isobaric thermal expansivity (αE) were also calculated. The variations of these parameters with concentration and temperature were discussed to elucidate molecular interactions due to physical, chemical and structural effects between the unlike molecules of the binary system. Several theoretical models viz. Van Dael’s ideal mixing relation, Nomoto’s relation, Schaaffs’ Collision Factor Theory, Impedance relation and Junjie’s method were also used to estimate ultrasonic speeds of the binary mixtures.